The relationship of physical balance and energy value in sheep rations studies carried out at the Kansas Agricultural Experiment Station Manhattan, Kansas. - Bell, T.D.; Cox, R.F.; Hughes, J.S. (Kansas Agricultural Experiment Station, 2012)
Lamb fattening rations varying in physical nature buy virtually alike chemically have been studied at the Kansas Agricultural Experiment Station for a number of years. Previous tests have demonstrated that the rate of gains and the efficiency of feed utilization by fattening lambs are associated closely with the physical balance or the concentration and bulkiness of the ration. The results of the experiments conducted during the summer of 1950 as well as preliminary results of the 1951 trails are reported.
Keywords: Lamb; Energy; Gains; Efficiency